Representation of decimal fractions as simple fractions in elementary grades - O'rozova Hosiyat Ikrom qizi (Zien Journals, 2022)
In this article, we will analyze how ordinary fractions are converted to decimal fractions, and also consider the reverse process - the conversion of decimal fractions to ordinary fractions.
Keywords: Common fraction; repeating decimals; operation; decimals